Assessment of maximal urinary flow rate (Qmax) of urethral stricture patients three weeks post internal urethrotomy Sachse in Dr. Sardjito General Hospital Yogyakarta - Ishandono Dachlan, Juni Ariston Tambunan Prawito Singodimedjo (Universitas Gadjah Mada, 2012)
Urethral stricture is a common urologic problem in developing countries including Indonesia dueto its high prevalence. Internal urethrotomy is still the gold standard to return patients to a stateof normal voiding. To evaluate the outcome of the internal urethrotomy, uroflowmetry assessmentcan be conducted with its principal variable of maximal urinary flow rate (Qmax). Since 1985, inDr. Sardjito General Hospital Yogyakarta, the internal urethrotomy has been used as the maintreatment modality to manage the urethral stricture. However, its outcome has not beenevaluated. The aim of this study was to evaluate Qmax of urethral stricture patients postinternal urethrotomy Sachse in Dr. Sardjito General Hospital. This was a cross-sectional studyperformed starting from November 2009 to April 2010. The Qmax was assessed using theuroflowmeter three weeks after internal urethrotomy. The length and the locations of the patientsâstricture, as well as its correlation with Qmax were also measured and evaluated. Among 24patients selected, 13 patients who fulfilled the inclusion and exclusion criteria were involved inthis study. The mean of the Qmax of patients was 22.3Â±6.7 mL/s.The mean of Qmax ofpatients who had the length of urethral stricture of dâ 2 cm (14.8Â±3.8 mL/s) was significantlyhigher than patients who had length of Ã 2 cm (6.4Â±2.6 mL/s) (p=0.03), whereas patients whohad the location of urethral stricture on anterior (12.4Â±5.4 mL/s) were not significantly differentcompared to patients who had those on posterior (8.5Â±4.9 mL/s) (p=0.398). In conclusion, themajority of patients returned to a state of normal urinary tract function post internal urethrotomy.The Qmax of urethral stricture patients after internal urethrotomy are influenced by the lengthof the stricture but not by its location.Keywords: urethral stricture - urethrography - Sachse - uroflowmetry - Qmax